Azimuth (from Pasir Salak to Kuala Kangsar) : a question of beauty and beyond / Izaddin Matrahah - Izaddin, Matrahah (Universiti Teknologi MARA, Perak, 2016)
A regard for beauty have always been a fundamental in appreciating the arts. In this short article I am trying to discuss its importance and the elements that created the perception in defining beauty and its criteria. Beauty maybe considered as a very subjective element as for most of us and as the saying goes - beauty is in the eye of the beholder. The topic in my study consist the elements and principles that constructed its language, the use of colour and how we perceived beauty according to our culture and belief. Through my observation there are also scientific approaches that were used to observe and understand the characteristic of design in art. By the way, the aim of this article is also to recognize how the design and images produced by artists reflects the personal forms of beauty that existed in their minds. The significance of this paper is also to explain the meaning of beauty through different kinds of definitions in hoping to bring understanding to the reader in this world full of different kinds of aesthetic.